(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
The essay analyses the evolution of Marfisa in some poems that appeared between the third version of Orlando Furioso and the second half of the 16th century. After reviewing Dragoncino da Fano’s Marfisa Bizarra, the essay will focus especially on some poems in which the Marfisa’s love story overlaps with the continuation of the story of Ullania and the three kings narrated in the Orlando Furioso. Finally, the essay will analyse the psychological insight of the character proposed in Cataneo’s Marfisa.